THE ORGANIZATION OF POLISH MONARCHISTS - IDEA AND HISTORY - Paweł KORZONDKOWSKI (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
Monarchist movements are not overly popular in Poland, one can rarely hear about activities of the monarchists, their postulates and views. This paper makes an attempt to depict the ideals and history of the Organization of Polish Monarchists; a Polish association which has been present in the public space since 1989. The first part of the paper describes the early stages of this organization’s activities, the next part contains a review of the three basic ideals underlying the Polish Monarchist Movement: catholic traditionalism, legitimism and the free market. Those three ideals create a certain “ideological triad”, the acceptance of which is a pre-requisite for everyone wishing to join the association. The last part lists the most important events and undertakings of the Organization of Polish Monarchists that took place in recent years.